Safety and effectiveness of adalimumab in patients with rheumatoid arthritis over 5 years of therapy in a phase 3b and subsequent postmarketing observational study - Burmester, Gerd R (BioMed Central, 2014)
INTRODUCTION: Patients with active rheumatoid arthritis who had failed at least one disease-modifying anti-rheumatic drug (DMARD) were treated with adalimumab (ADA) in the ReAct study with the option to continue treatment for 5 years in ReAlise. The purpose of this study was to evaluate the long-term safety and effectiveness of ADA as prescribed from the first injection in ReAct to the last observation in ReAlise. METHODS: Patients received ADA alone or in combination with DMARDs according to usual clinical care practices. Adverse events (AEs) were tabulated by five time windows after the first ADA injection. Effectiveness measures included achievement of low disease activity (LDA), defined as Simplified Disease Activity Index (SDAI) ≤11, or remission, (REM), defined as SDAI ≤3.3. RESULTS: Of the 6,610 ReAct patients, 3,435 (52%) continued in ReAlise. At baseline in ReAct, mean age was 54 years, mean DAS28 was 6.0 and mean HAQ DI was 1.64. The mean treatment duration was 1,016 days, representing 18,272 patient-years (PYs) of ADA exposure. Overall incidence rates of serious AEs and serious infections were 13.8 and 2.8 events (E)/100 PYs, respectively. Serious AEs occurred most frequently in the first 6 months and deceased thereafter. Standardised mortality ratio was 0.71 (95% CI 0.57 to 0.87) and standardised incidence ratio for malignancies was 0.64 (95% CI 0.53 to 0.76). LDA was achieved by 50% and REM by 21% of patients at last observation. CONCLUSIONS: Results of this large observational study of ADA in routine clinical practice were consistent with controlled trials, with no new safety concerns during a follow-up of more than 5 years. Effectiveness of ADA was maintained during long-term observation. TRIAL REGISTRATION: NCT00448383, NCT00234884